Male-specific contributions to the Brazilian population of Espirito Santo - Figueiredo, Raquel de Freitas [UNESP]; Ambrosio, Isabela Brunelli [UNESP]; Braganholi, Danilo Faustino [UNESP]; Chemale, Gustavo; Martins, Joyce Aparecida [UNESP]; Gomes, Veronica; Gusmão, Leonor; Cicarelli, Regina Maria Barretto [UNESP] (International Journal Of Legal Medicine, 2015)
Y chromosome markers have been widely studied due to their various applications in the fields of forensic and evolutionary genetics. In this study, 35 Y-SNPs and 17 Y-STRs were genotyped in 253 males from the State of Espirito Santo, Brazil. A total of 18 haplogroups and 243 haplotypes were detected; the haplogroup and haplotype diversities were 0.7794 and 0.9997, respectively. Genetic distance analysis using the Y-STR data showed no statistically significant differences between Espirito Santo and other admixed populations from Brazil. The classification of paternal lineages based on haplogroups showed a predominant European contribution (85.88 %), followed by African (11.37 %) and Amerindian (2.75 %) contributions.
Keywords: Y chromosome; Y-SNP haplogroup; Y-STR haplotype; Brazil